2004
DOI: 10.1080/00365590310017280
|View full text |Cite
|
Sign up to set email alerts
|

Role of bladder neck preservation in urinary continence following radical retropubic prostatectomy

Abstract: Bladder neck preservation during radical retropubic prostatectomy does not improve the long-term results of urinary continence but does contribute substantially to its earlier recovery, thus improving the quality of life. With proper patient selection the risk of positive margins at the bladder neck level only is reasonably low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 23 publications
1
42
1
7
Order By: Relevance
“…Additionally, by using the nerve-sparing procedure we improved our continence rates (18), which are possibly attributed to the meticulous dissection of the nerves from the apex of the prostate instead of the preservation of the neurovascular bundle. Furthermore, preservation of the bladder neck especially of its circular fibers, as in this series of patients, contributes to return of continence (19).…”
Section: Commentsmentioning
confidence: 99%
“…Additionally, by using the nerve-sparing procedure we improved our continence rates (18), which are possibly attributed to the meticulous dissection of the nerves from the apex of the prostate instead of the preservation of the neurovascular bundle. Furthermore, preservation of the bladder neck especially of its circular fibers, as in this series of patients, contributes to return of continence (19).…”
Section: Commentsmentioning
confidence: 99%
“…Selli [15] Bladder neck preservation in RRP leads to faster return of continence but does not affect long-term recovery.…”
Section: Primary Author Resultsmentioning
confidence: 99%
“…Standardization of RALP outcome definitions (such as continence) is imperative before adequate comparisons of these variables can be made. A variety of surgical techniques have been employed in an attempt to improve early return of continence after RP (both open and minimally invasive), including bladder neck (BN) preservation [15,16], intussusception of the BN [17], puboprostatic ligament sparing, sling construction [18], incorporation of the striate urethral sphincter to the anastomosis, and tubularization of the bladder neck. Historically, the actual benefits of these modifications have been somewhat controversial.…”
Section: Urinary Continence and The Urethrovesical Anastomosismentioning
confidence: 99%
“…It has to be noted that in this study, we preserved the bladder neck using our own technique in all patients to avoid a potential bias that could have affected the analysis of continence outcomes [13,14]. Sparing of bladder neck has been associated with better functional outcomes after surgery due to a lower risk of urethral injury and bladder neck stricture [24,25,26]. It has been suggested that bladder neck preservation may compromise oncological outcomes by increasing the risk of positive surgical margins.…”
Section: Discussionmentioning
confidence: 99%